2014
DOI: 10.5574/ijose.2014.4.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Responses of Spar Hull with Single and Double Heave Plates in Random Waves

Abstract: Heave plates have been widely used to enhance viscous damping and thus reduces the heave response of Spar platforms. Single heave plate attached to the keel of the Spar has been reported in literature (Tao and Cai 2004). The effect of double heave plates on hydrodynamic response in random waves has been investigated in this study. The influence of relative spacing L d /D d (D d -the diameter of the heave plate) on the hydrodynamic response in random waves has been simulated in wave basin experiments and numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is at this distance that multiple heave plates should be stacked, as the added benefit of each additional heave plate is maximized. Performing a similar study, Sudhakar et al found that above a relative spacing of 0.8, the heave plates could be considered independent [32].…”
Section: A Literature Reviewmentioning
confidence: 90%
“…It is at this distance that multiple heave plates should be stacked, as the added benefit of each additional heave plate is maximized. Performing a similar study, Sudhakar et al found that above a relative spacing of 0.8, the heave plates could be considered independent [32].…”
Section: A Literature Reviewmentioning
confidence: 90%
“…Through a series of experiments, some approximation equations were developed to calculate the added mass of the floating cylinder with a separate heave plate, and the motion response of a vertical circular cylinder with a heave plate to a series of regular waves was examined by Zhu and Lim [20]. Sudhakar and Nallayarasu [21,22] investigated the influence of single and double damping plates on the hydrodynamic response of a spar in regular and irregular waves by experimental studies. Koh et al [23] performed free decay tests by experiments to obtain the viscous damping coefficients of a circular cylinder with a heave damping plate changing the porosity of the damping plate.…”
Section: Introductionmentioning
confidence: 99%